Profil Disabilitas Netra Berprestasi Dibidang Atletik Lari pada Tingkat Naisonal di Sawahlunto - Fentari, Nadya Deski; Irdamurni, Irdamurni (Jurnal Penelitian Pendidikan Khusus, 2024)
This research aims to find out and describe the achievements achieved in the field of running athletics, the role of parents in developing X's achievements, the obstacles that X faces in achieving achievements, and the solutions that X needs to achieve achievements in the field of running athletics. This research uses a qualitative descriptive research type. The techniques used in this research are data collection techniques, observation techniques, interview techniques and documentation studies. Based on the results of this research, it shows that the role of parents is very influential in developing X's achievements in the field of running athletics.